New Interdisciplinary Perspectives On and Beyond Autonomy (Taylor & Francis, 2023)
Autonomy, philospohy, politics, language, Pharmacology, climate
English
Keywords: Literature: history and criticism; Political ideologies and movements; Social and cultural anthropology; Social discrimination and social justice; Autonomy, philospohy, politics, language, Pharmacology, climate